(untitled) (Economic and Political Thought, 2016)
In the face of increasing interest in corporate governance issues, the correctness of research methods in this area becomes a matter of crucial importance. In the article, the author draws attention to the methodological areas that generate the highest probability of errors in the use of microeconometric tools. Special attention, in the author’s opinion, should be paid to the distinction of agency problems occurring in corporations with different ownership structures, as well as to reverse causality, missing variables, sample selectivity, and measurement errors in variables. Minimizing the risk of getting the estimation errors associated with the occurrence of these phenomena should increase the reliability of the results obtained and the credibility of the commonly used ratings of corporate governance.